STRATEGI KEPALA SEKOLAH DALAM PENGEMBANGAN KOMPETENSI PROFESIONAL GURU UNTUK MENINGKATKAN MUTU - Mochammad Fathan Solikhulhadi (MADINASIKA, 2021)
This research is motivated by the low professional competence of teachers which has an impact on the low quality of education, presumably due to the inappropriate strategy of the principal. The research aims to analyze and find out: a) the principal's strategy in developing teacher professional competence; b). Barriers faced in developing teacher competence; and; c) the principal's efforts to overcome barriers to developing teacher professional competence. The study used a qualitative approach with the main data collection tool using in-depth interviews. The informants are defined positively, the data obtained through data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation techniques. The results showed: a) The strategies used by the principal in the development of teacher competence consisted of formal strategies and non-formal strategies; b) The obstacles faced are the low interest of teachers in self-development, the limitations of teachers in mastery of ICT, and the availability of inadequate facilities; c) Efforts made to overcome obstacles are through in-service training. In conclusion, the principal's strategy in developing teacher professional competence can improve the quality of education.